Theory and practice of selective imidazoline receptor agonist use in Russia - N. I. Gaponova; V. R. Abdrakhmanov (Рациональная фармакотерапия в кардиологии)
Activation of the sympathetic nervous system plays an important role in arterial hypertension (AH) development. Antihypertensive drugs of central action contribute to the elimination of sympathetic activation. The selective imidazoline receptor agonist moxonidine has been successfully used in the treatment of patients with hypertension. The review article presents data on the antihypertensive efficacy of moxonidine, the possibility of its use in combination therapy to reduce elevated blood pressure (BP). The effectiveness of moxonidine in overweight patients, metabolic syndrome, diabetes mellitus, and postmenopausal women is shown. In addition to lowering blood pressure in obese patients, moxonidine reduces plasma leptin levels and weakens sympathetic overactivity, which contributes to weight loss. In patients with metabolic syndrome — obesity, type 2 diabetes mellitus, the use of moxonidine, along with the antihypertensive effect, was accompanied by an additional positive effect on increased variability in blood pressure levels, contributing to the normalization of the daily blood pressure profile, eliminating the morning rise in blood pressure levels. The beneficial effect of moxonidine on carbohydrate metabolism and tissue sensitivity to insulin was noted. The administration of moxonidine to patients with hypertension and menopausal syndrome in peri- and postmenopause, along with effective level control, was accompanied by a significant improvement in the quality of life. In patients with hypertension and osteopenia during menopause, moxonidine led to increased bone formation processes, which helps reduce the risk of developing or progressing osteopenia and osteoporosis. The article focuses on additional indications for the use of moxonidine. In the presence of concomitant pathology — chronic obstructive pulmonary disease, chronic kidney disease, dementia in elderly patients, the use of moxonidine, along with antihypertensive action, led to an improvement in the quality of life.